Beclomethasone dipropionate for the treatment of ulcerative colitis. (January 2015) - Gabbani, Tommaso; Manetti, Natalia; Bagnoli, Siro; Annese, Vito
<x xml:space="preserve">Abstract</x> Introduction: Corticosteroids are still the mainstay of treatment in patients with active ulcerative colitis (UC) refractory to mesalamine (5-aminosalicylic acid, 5-ASA), but their benefits are offset by the frequent occurrence of adverse events. In recent years, new corticosteroid molecules have been developed combining an oral controlled-release formulation, high affinity for the corticosteroid receptor and a rapid first-pass liver metabolism. Areas covered: Oral <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=beclomethasone &logicalOpe1=OR&field2=articletitle&text2=beclomethasone &logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">beclomethasone (BOH) is an example of these oral locally acting steroids used in inflammatory bowel diseases and this review will focus on its efficacy in UC. Beclomethasone dipropionate (BDP) is a prodrug that is activated and metabolised locally, available as topical and oral formulation. BDP enema is equally effective as first-generation corticosteroids enemas but has a better safety profile. Topical combination of BDP and 5-ASA is by far the most effective topical therapy in UC. Oral BDP showed similar efficacy compared to systemic corticosteroids in UC, but with less systemic adverse effects. Therefore, BDP is a logic alternative to standard steroids for patients with mild-to-moderate active UC. Expert opinion: The availability of 'locally active' steroids like BDP, used orally or topically in combination with 5-ASA, is a great step forward due to its significant efficacy and sparing of systemic side effects.